1999
DOI: 10.1073/pnas.96.6.2805
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4 signals cooperatively with integrins in a Rhodependent manner in the assembly of focal adhesions and actin stress fibers

Abstract: The assembly of focal adhesions and actin stress fibers by cells plated on fibronectin depends on adhesionmediated signals involving both integrins and cell-surface heparan sulfate proteoglycans. These two cell-surface receptors interact with different domains of fibronectin. To attempt to identify the heparan sulfate proteoglycans involved, we used fibronectin-null (FN؊͞؊) mouse fibroblasts to eliminate the contribution of endogenous fibronectin during the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
319
3
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 343 publications
(344 citation statements)
references
References 35 publications
16
319
3
4
Order By: Relevance
“…2, top right panel). FN−/− cells, which were derived from embryonic stem cells from a FN-knock-out mouse (George et al, 1993) and selected based on their fibroblastic character, have been demonstrated not to secrete FN (Saoncella et al, 1999). In addition, we detected no FN in cell layers with rabbit anti-human 70K antibodies that recognize mouse FN (Fig.…”
Section: K Binds To Cells In Linear Arrays In the Absence Of Intact Fnmentioning
confidence: 65%
See 1 more Smart Citation
“…2, top right panel). FN−/− cells, which were derived from embryonic stem cells from a FN-knock-out mouse (George et al, 1993) and selected based on their fibroblastic character, have been demonstrated not to secrete FN (Saoncella et al, 1999). In addition, we detected no FN in cell layers with rabbit anti-human 70K antibodies that recognize mouse FN (Fig.…”
Section: K Binds To Cells In Linear Arrays In the Absence Of Intact Fnmentioning
confidence: 65%
“…FN−/− and FN+/− mouse fibroblasts had been derived from FN−/− and FN+/− embryonic stem cells obtained from homozygous and heterozygote FN knock-out mice (George et al, 1993;Saoncella et al, 1999). Cells were cultured in Dulbecco's modified Eagle's medium (DMEM, Life Technologies, Inc.) with 10% fetal bovine serum (Intergen, Purchase, NY) and 100 IU/ ml penicillin and 100 μg/ml streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
“…Regulation through phosphorylation of syndecan-4 cytoplasmic tail may also exist in syndecan-4 signaling (Horowitz et al, 1999). The involvement of Rho activity in the formation FAs and stress fibers through syndecan-4 signaling has also been suggested (Saoncella et al, 1999;Couchman et al, 2001). Besides all signaling molecules described above, stretch-activated ion channels are considered to be candidates for mechanotransduction mechanisms (Hu and Sachs, 1997;Sadoshima and Izumo, 1997).…”
Section: Cellular Mechanotransductionmentioning
confidence: 99%
“…Syndecan-4 is involved in cytoskeletal reorganization, assembly of stress fibers, and FA formation. In fact, it has been shown to be required for FA formation in addition to integrins (Saoncella et al, 1999;Woods et al, 2000). Recruitment of syndecan-4 to FAs is dependent on PKC activation, and multimerization of the cytoplasmic domain of syndecan-4 is required for kinase binding and activation (Baciu and Goetinck, 1995).…”
Section: Cellular Mechanotransductionmentioning
confidence: 99%
“…Concomitant engagement of Sdc4 and integrins promotes Rho GTPase and focal adhesion kinase (FAK) activities, which are crucial for efficient initiation of FN matrix assembly. [12][13][14][15] Sdc1 is expressed primarily by epithelial and plasma cells of healthy adult tissue. 16 Recently, we and others 17,18 observed the induction of Sdc1 in stromal fibroblasts of invasive breast carcinomas.…”
mentioning
confidence: 99%